2016
DOI: 10.1097/acm.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

How Do Residents Spend Their Shift Time? A Time and Motion Study With a Particular Focus on the Use of Computers

Abstract: Purpose To understand how much time residents spend using computers as compared with other activities, and what residents use computers for. Method This time and motion study was conducted in June and July 2010 at NewYork-Presbyterian/Columbia University Medical Center with seven residents (first-, second-, and third-year) on the general medicine service. An experienced observer shadowed residents during a single day shift, captured all their activities using an iPad application, and took field notes. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 24 publications
4
96
0
1
Order By: Relevance
“…Other studies have shown that a less complex case mix, increased patient volume, and nursing magnet designation were independently associated with increased direct patient care time . Studies of resident physicians have shown a decrease in DPCT and an increase in indirect patient care as a result of work hour restrictions . However, those studies did not evaluate DPCT longitudinally or in association with very specific environments such as training on a hematology‐oncology ward or in association with empathy, death salience, or empathy decline factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that a less complex case mix, increased patient volume, and nursing magnet designation were independently associated with increased direct patient care time . Studies of resident physicians have shown a decrease in DPCT and an increase in indirect patient care as a result of work hour restrictions . However, those studies did not evaluate DPCT longitudinally or in association with very specific environments such as training on a hematology‐oncology ward or in association with empathy, death salience, or empathy decline factors.…”
Section: Discussionmentioning
confidence: 99%
“…Time-motion studies have shown current requirements result in a 2:1 ratio of time spent on documentation compared to direct patient care, with only approximately 10% of physician time spent actually providing care to patients. 24 A more recent study showed that the ratio of documentation to direct patient care may be as high as 5:1. 25 The ideal environment for finding meaning in work appears to conflict directly with the existing environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given an alert, a clinician has to decide quickly what to do about it in the presence of many competing inputs and responsibilities [14,15]. A concise explanation of an alert is helpful for triaging of alerts and clinical decision making.…”
Section: Use Case Of An Early Warning Systemmentioning
confidence: 99%